If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(-2 + 3x) + -1x = 6x + -33 (-2 * 8 + 3x * 8) + -1x = 6x + -33 (-16 + 24x) + -1x = 6x + -33 Combine like terms: 24x + -1x = 23x -16 + 23x = 6x + -33 Reorder the terms: -16 + 23x = -33 + 6x Solving -16 + 23x = -33 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -16 + 23x + -6x = -33 + 6x + -6x Combine like terms: 23x + -6x = 17x -16 + 17x = -33 + 6x + -6x Combine like terms: 6x + -6x = 0 -16 + 17x = -33 + 0 -16 + 17x = -33 Add '16' to each side of the equation. -16 + 16 + 17x = -33 + 16 Combine like terms: -16 + 16 = 0 0 + 17x = -33 + 16 17x = -33 + 16 Combine like terms: -33 + 16 = -17 17x = -17 Divide each side by '17'. x = -1 Simplifying x = -1
| 7(x+9)=12x+103 | | 1.2=4.8(-x+-3.5) | | 4(5-x)=3(x-5) | | 1.2=4.8-(x+3.5) | | 1(t-5)+7t=4(2t+5)9 | | 1.2=4.8(x+3.5) | | -2(5s-3)-6=-3(5s+5)-4 | | 13(x+6)=12x+87 | | 3(-3)-y=1 | | 10xy-6x=0 | | 104-7x=29x+16 | | 3(2x-50)= | | 7(2x+4)=10(x+4) | | 4(2x-2)-4x=10 | | 2y+2*4=6 | | -3(5s-5)-15=-3(7s+0)-5 | | 2y+2*-1=6 | | 12=-1-5m-8m | | -3x-2x=20 | | 5x+6+9x+7=125 | | v+(v+23.2)+(v+33.5)=192.2 | | -7x-14=-21 | | 19+2(3n-15)=1 | | 5-6v-6=11 | | v+(v-23.2)+(v+33.5)=192.2 | | 4(6y-2)=16y | | -17x+19y=-2 | | 5(7+4n)=-37+8n | | v+(v-33.5)+(v+23.2)=192.2 | | 8b-4+8b=-4 | | ln(x-2)-ln(x+2)=ln(x-1)-ln(2x+4) | | 2x^2+15x+28=56 |